Euro-Atlantic weather regimes across various global warming levels on multi-centennial timescales - Tessari, Ilaria (Alma Mater Studiorum - Università di Bologna, 2024)
In this study, we investigate the variations of the large-scale extratropical atmospheric circulation in the Euro-North Atlantic (EAT) sector at different global warming thresholds. The analysis is based on the work of Fabiano et al. (2023) [1], where a set of 1000-year long abrupt stabilization simulations performed with the EC-Earth3 climate model [2] is presented. Here we focus on the atmospheric circulation, analyzing daily mean geopotential height data at 500 hP a using the Weather Regimes (WRs) perspective, to investigate the climate response at multi-centennial timescales for different levels of radiative forcing, relative to the pre-Industrial (PI) conditions. Weather Regimes are defined as persistent and recurrent large scale patterns of geopotential height anomalies (Z500’), derived respect to the atmospheric reference mean state (climatology) characterizing the domain of interest. In the WRs researches, the study of a particular season is usually privileged (mostly winter), while here we analyse the variations of the whole year-round circulation, using the method implemented in the work of Grams et al. (2017) [3] . Based on our findings, we infer that the warming induced by anthropogenic forcing at high CO2 levels has the potential to alter the low-frequency, large-scale mid-latitude circulation pat- terns (examined through the lens of Weather Regimes) in the Euro-North Atlantic region over a multi-centennial period, in comparison to the pre-Industrial time. We detect changes in the yearly mean frequency of occurrence and in the seasonal cycle (monthly and seasonal mean frequencies) of the various Weather Regimes characterizing the domain. The most striking change regards the increase in the occurrence of blocking regimes especially during summer (in particular, of the Scandinavian Blocking), which are known to be connected to heatwaves events, expected to increase in a warmer climate.